2013
DOI: 10.1016/j.ridd.2013.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of postural control in children with cerebral palsy: A review

Abstract: This paper aimed to review studies that assessed postural control (PC) in children with cerebral palsy (CP) and describe the methods used to investigate postural control in this population. It also intended to describe the performance of children with CP in postural control. An extensive database search was performed using the keywords: postural control, cerebral palsy, children, balance and functionality. A total of 1065 papers were identified and 25 met the inclusion criteria. The survey showed that PC is wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 48 publications
0
56
0
4
Order By: Relevance
“…Health professionals were contacted from (1) the CPL and CP Alliance through the organization's representative; (2) members of the AusACPDM (nonmedical AusACPDM members, eg, lawyers or parents, were not contacted); and (3) authors of research articles about postural control who were identified in recent systematic reviews [8][9][10] and who have published contact details. Potential participants numbered approximately 711, based on the number of invitations disseminated (fig 1).…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Health professionals were contacted from (1) the CPL and CP Alliance through the organization's representative; (2) members of the AusACPDM (nonmedical AusACPDM members, eg, lawyers or parents, were not contacted); and (3) authors of research articles about postural control who were identified in recent systematic reviews [8][9][10] and who have published contact details. Potential participants numbered approximately 711, based on the number of invitations disseminated (fig 1).…”
Section: Participantsmentioning
confidence: 99%
“…Respondents who submitted Round 1 also gave consent to participate in subsequent rounds. Round 1 contained open-ended questions constructed by the authors (box 1) based on theoretical principles of postural control and systematic reviews of postural control assessments, 8,9 interventions, 10 and approaches. 10 The questions sought responses for postural control (1) definitions; (2) framework for development, assessment, and intervention; (3) assessments; and (4) interventions for children with CP.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 3 more Smart Citations